Giving inertial sensor data context for communication in applied settings: an example of visual exploration in football - McGuckian, T. B.; Chalkley, D.; Shepherd, J.; Pepping, G.-J. (Proceedings, 2018)
For an athlete to make an appropriate decision and successfully perform a skill, they need to perceive opportunities for action by visually exploring their environment. The head movements that support visual exploration can easily and accurately be recorded using Micro-Electro-Mechanical Systems (MEMS) Inertial Measurement Units (IMU) in research and applied settings. However, for IMU technology to be effective in applied settings, practitioners need to be able to communicate data to coaches and players. This paper presents methods of visualising and communicating exploratory head movement data, with the aim of giving a better understanding of (a) individual differences in exploratory action, and (b) how IMUs can be used in applied settings to assess and monitor visual exploratory action.